(untitled) (Research, Society and Development, 2021)
The insertion of pets in hospital settings through assisted interventions has become an alternative therapeutic method in human medicine, and studies have been conducted to ensure that these activities are performed safely for all involved. Therefore, this study aimed to investigate the perception of health professionals, working in clinics and hospitals, about the risks and benefits of Animal-Assisted Interventions (AAIs). This is a survey study in which 44 human health professionals participated. The collection was done through a questionnaire with questions about AAIs in hospitals, focusing on animal, patient, and other people’s well-being, as well as possible risks, carried out online between April and May 2020. The profile of these participants was mostly residents in the North region of Brazil, aged 30 to 40 years, nurses working in hospitals. As for AAIs, 91% have no experience and 86.3% of them are in favor of dogs entering this environment. The participants recognized that there are benefits to patients, professionals, companions and the environment, making it more welcoming and humanized, and that although there are risks: of contamination of the patient, of the reactions of people and dogs, or even those resulting from the lack of preparation of the hospital staff, the AAI, as it is a systematized practice by a multidisciplinary team, contributes to the reduction of these risks.